2013
DOI: 10.1136/sextrans-2013-051184.0493
|View full text |Cite
|
Sign up to set email alerts
|

P3.033 Epidemiology of Viral STIs in 2000–2011 in Russian Federation

Abstract: Objective To find out how condom use in new relationships changes as a function of time, gender, as well as sexual and relationship satisfaction. Method Participants in a larger study who reported at least one new partner during the 12-week study interval (N = 115; 18-29 yrs; 48% women; 75% African American) completed weekly STI testing and 3x/day electronic diary collection assessing individual and partner-specific affect, daily activities, sexual behaviour and condom use. We analysed event-level condom use p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bogdanova et al evaluated the epidemiology of viral STIs from 2000 to 2011 in the Russian Federation and concluded that the total rates of genital herpes simplex virus infection remained constant (mean rate 19.8±1.4 per 100 000) while the total HPV infection rate during the same period increased from 27.4 to 29.2 per 100 000, with maximum reported rates of 34.7 in 2009. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bogdanova et al evaluated the epidemiology of viral STIs from 2000 to 2011 in the Russian Federation and concluded that the total rates of genital herpes simplex virus infection remained constant (mean rate 19.8±1.4 per 100 000) while the total HPV infection rate during the same period increased from 27.4 to 29.2 per 100 000, with maximum reported rates of 34.7 in 2009. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Bogdanova et al evaluated the epidemiology of viral STIs from 2000 to 2011 in the Russian Federation and concluded that the total rates of genital herpes simplex virus infection remained constant (mean rate 19.8±1.4 per 100 000) while the total HPV infection rate during the same period increased from 27.4 to 29.2 per 100 000, with maximum reported rates of 34.7 in 2009. 10 The large economic burden of GW treatment and management weighs heavily on a health care system. With rates of newly diagnosed GW cases increasing, the economic burden is also likely to increase, as even self-resolved GW cases can recur and in some cases are resistant to treatment.…”
mentioning
confidence: 99%